MyPainting.nu. - Nelemans, Rebecca; Otter, Olphaert den; Van Eecke, Christophe; Verlaek, Jolien; Voogd, Karin; Voskuil, Jan Maarten; Exhibition. MyPainting.nu. Breda. Lokaal 01 Breda. 2009-04-19. 2009-07-12 (Breda : Lokaal 01 Breda, 2009)
Timmermans, Ante ; Frize, Bernard ; Frings, Bert ; Palermo, Blinky ; Hardt, Bruno ; Van Eecke, Christophe ; Hollerer, Clemens ; Eecken, Dirk Vander ; Marcaccio, Fabian ; Houben, Hedwig ; Dorner, Helmut ; van der Loo, Huub ; Andriesse, Jan ; Voskuil, Jan Maarten ; McNab, Janice ; Vanderheyden, JCJ ; Bytebier, Jean-Marie ; De Wilde, Johan ; van der Sommen, Jos ; Wouters, Karel ; Goudzwaard, Kees ; Van Dessel, Kris ; Hendriks, Lieven ; Devriendt, Lucas ; Tuymans, Luc ; Schuppers, Martijn ; Otter, Olphaert den ; Vanden Eynde, Patrick ; Vermeersch, Pieter ; Hocks, Teun ; de Cordier, Thierry ; Raat, Thomas ; Tilman ; Gillen, Tina ; Sasnal, Wilhelm ; Malevich, Kasimir ; Zegers, Ben ; Fludd, Robert ; Bandau, Joachim ; Quix, Stefaan
Nederlands
boek